Digital Financial Services and Human Development: Current Landscape and Research Prospects - Sharma, H; Díaz Andrade, A (Informa UK Limited, 2023)
This study explores and analyses the implications of digital financial services (DFS) on human development from a global perspective. Informed by a systematic literature review of studies published in the past two decades, from 2000 to 2020, this research unveils six overarching themes: contextual conditions, technological skills and financial literacy, consistent trust, shaping financial behavior, energizing economic activities, and supporting financial inclusion. Further analysis categorizes these themes into what constitutes the two intertwined dimensions of DFS: foundational conditions and effectual repercussions. We discuss how these dimensions enhance our understanding of the role information and communication technologies play in contributing to human development. We also present practical implications for different stakeholders in the financial sector.
Keywords: 46 Information and Computing Sciences; 44 Human Society; 08 Information and Computing Sciences; 16 Studies in Human Society; 44 Human society; 46 Information and computing sciences